Professional self-concept of Bachelor Degree and Diploma Nursing students of Universiti Sains Malaysia (USM) - Nanyan, Norhafizah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The professional nurse self-concept determines the self-image of a nurse and their ability to achieve their expectation. As nursing is an important profession in the health care team, the professional self-concept is needed for nurses to play their role effectively. In this study, the professional self-concept is measured among nursing students in Universiti Sains Malaysia (USM). The objectives of this study are; to determine the level of professional self-concept among final year students of bachelor degree and diploma nursing programme in USM, to compare the level of professional self-concept between these nursing programmes, and to determine the association between the students' demographic characteristics and the level of the professional self-concept. This crosssectional study was conducted among 72 final year nursing students of Bachelor and Diploma program. They were selected randomly and data was collected using a set of self-admitted questionnaire within three month period from December 2012 to February 2013. The findings showed higher level of self-concept was elicited among students of diploma programme. A significant association was found between the levels of professional self-concept and nursing programs. The socio-demographic characteristics had no influence on the level of self-concept among students. Future research is required to retest this findings and find out the rationales of such findings.